Patients with detectable KIT p.D816V in peripheral blood are at high risk for adverse systemic events during venom immunotherapy and treatment failure - Ajda Demšar Luzar; Jakob Otorepec; Mitja Košnik; Peter Kopač; Julij Šelb; Peter Korošec; Matija Rijavec (Clinical and Translational Allergy)
Abstract Background Recent studies have highlighted the importance of routine screening for the somatic missense KIT p.D816V variant in peripheral blood leukocytes (PBL), and its association with severe sting anaphylaxis. Our study aimed to evaluate the clinical relevance of KIT p.D816V detected in PBL on systemic adverse events (SAEs) and the efficacy of venom immunotherapy (VIT). Methods This retrospective study included 839 patients receiving VIT. The KIT p.D816V variant was assayed with a highly sensitive, allele‐specific, quantitative PCR. Results KIT p.D816V was detected in the PBL of 125 (15%) of 839 VIT patients. The majority (70%, 88/125) of these individuals had normal BST levels. Notably, half of the KIT‐positive patients receiving honeybee venom immunotherapy had SAEs during treatment (48%, 18/37; p = 0.0136), and the KIT p.D816V allele burden was higher than 0.01% in the majority of those patients (61%, 11/18). Furthermore, a significant difference was observed between KIT‐positive and KIT‐negative patients treated with VIT in the past and who experienced a recurrent reaction to a sting after treatment termination (VIT failure). KIT‐positive patients with VIT failure had a higher allele burden than those with successful VIT (80% vs. 40% with a KIT p.D816V higher than 0.01%; p = 0.0019). KIT p.D816V was a predictor of SAEs during honeybee VIT (univariate; OR = 2.43, p = 0.012/multivariate; OR = 2.26, p = 0.033) and a strong predictor of VIT failure in patients treated with wasp venom (univariate; OR = 4.1, p = 0.002/multivariate; OR = 3.54, p = 0.008). Conclusion Our study revealed the high clinical relevance of KIT p.D816V detected in PBL. KIT p.D816V was a significant predictor of SAEs during honeybee VIT and a significant predictor of VIT failure after completing wasp VIT.